2005
DOI: 10.1063/1.1858061
|View full text |Cite
|
Sign up to set email alerts
|

Plasma emission induced by an Nd-YAG laser at low pressure on solid organic sample, its mechanism, and analytical application

Abstract: An Nd-YAG laser (1064 nm, 120 mJ, 8 ns) was focused on various types of solid organic samples such as a black acrylic plate, a black polyvinyl chloride plastic sheet, and a methoxy polyaniline film coated on the surface of a glass substrate, under a surrounding air pressure of 2 Torr. A modulated plasma technique was used to study the mechanism of excitation of the emission of the organic material. As a result, we conclude that ablated atoms and molecules are excited by a shock-wave mechanism, similar to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The integration time and laser energy were fixed during the mesurements. The behavior of emission signals at low pressure has also explained by Suliyanti et al [2] by focusing Nd: YAG laser on different organic samples at low pressure using substrate behind the target. There are two distinct parts of plasma emission at low pressure, in primary part for short period there was continuum emission and in secondary part, there was a strong emission of atomic spectral lines in expanded plasma [2].…”
Section: Time-resolved Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…The integration time and laser energy were fixed during the mesurements. The behavior of emission signals at low pressure has also explained by Suliyanti et al [2] by focusing Nd: YAG laser on different organic samples at low pressure using substrate behind the target. There are two distinct parts of plasma emission at low pressure, in primary part for short period there was continuum emission and in secondary part, there was a strong emission of atomic spectral lines in expanded plasma [2].…”
Section: Time-resolved Studiesmentioning
confidence: 63%
“…These techniques requires sample preparations and involve solutions during their analysis process which may contaminate them and affect the qualitative and quantitative results. Line profiles of essential nutrients of these plants have also discussed at different time delay, energy and ambient pressures [2][3][4][5]. The detection of CN band is important to analyze actual content of C and N with CN band emission by LIBS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, Suliyanti et al 103 conducted a study on plasma emission induced from a solid organic analyte at low-pressure. They findings revealed that emission lines generated at lower gas pressure displayed more distinct profiles compared to those generated at higher-pressure This observation was attributed to the diminished ablation process that occurs at lower pressure.…”
Section: Experimental Parametersmentioning
confidence: 99%